A Brief Account for Sources of Quranic Interpretation Principles of Quranic Interpretation - Zahra , Syed Amina; Khan , Prof. Dr. Ubaid Ahmed (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The Holy Quran is an Ocean of knowledge. It is not in the capacity of one person to grasp and have command on all of its aspects and interpret all its topics wholly and solely. However, it has been allowed to interpret it, but rules have been fixed for its interpretation and one cannot violate these rules while its interpretation. Numerous books have been written on ‘the Principles of Quranic Interpretation’ and hundreds of scholars have strived to interpret it following these rules which are mainly: Quran Interpretation through Quranic Verses Quran Interpretation through Hadith Quran Interpretation through quotations of the Companions of the Holy Prophet (peace be upon him) Quranic Interpretation through the comments of the Comrades of the Companions of the Holy Prophet (peace be upon him) This type of Quranic Interpretation is called Tafseer-bil-Mathur (interpretation through original sources). Another type of interpretation is also prevalent which is permitted through Quran and Sunnah, which is called ‘Tafseer-bil-Rai’, (interpretation through contemplation). It again has two sub-types. Quranic Interpretation through Intellectual Background Quranic Interpretation through Spiritual Perspective For all these types of Quranic Interpretations the exegete requires to achieve the traditional knowledge including Quran, Hadith, traditions of the companions of the Holy Prophet (peace be upon him), their comrades, all the branches of knowledge mentioned, as compulsory to acquire for an exegete, in the traditional books on ‘Principles of Quranic Interpretation’ and additionally, what he needs is, to have full command in the concurrent scientific knowledge also to avoid any kind of flaws during Quranic Interpretation, and also a Quranic Interpreter requires to be a shrewd writer to avoid committing mistakes or giving faulty or momentary statements during Quranic Interpretation.